Application of Kavrak (Ferula Assa-Foetida L.) in Folk Medicine - Khaidarovich, Eshonkulov Alijon; Abdurasulovich, Sherov Sherzod (European Journal of Life Safety and Stability (2660-9630), 2022)
Kavrak (Ferula assa-foetida L.) Has long been used as a spice and medicinal plant. In ancient times, the sticky and sticky resin of the fetid plant was used in combination with pomegranate juice to prevent muscle injuries and treat severe pain in the body. If the resin of the plant is dissolved in water, then a sore throat, dry cough, swelling of the tongue can be cured. In folk medicine, alcohol or an aqueous tincture of the root and stem of the plant is used against many diseases. In Asian countries, kavrak is widely used as a seasoning, especially for indigestible foods. The plant improves the digestion process, while awakening the appetite. In a word, it is not for nothing that the foul-smelling plant is called the "Famous Plant of the East".